Financial Management of NGOs towards financial sustainability: a case of Gaborone, Botswana - Kgotlaetsile, Keagetswe Alex (Department of Social Development, 2023)
Financial sustainability remains a key concern for Non-Governmental Organisations (NGOs) in Botswana. Their survival is dependent on the fading donor funding, illustrating a weak financial capacity and poor financial sustainability prospects. To continue operating, NGOs must adopt sound financial management practices to enhance their financially sustainability. The aim for this study is to find out if the financial management practices used by NGOs in Botswana can improve their financial sustainability, thus also determining their financial sustainability potential. The study employed a convergent parallel mixed method design, using structured surveys and face to face semi-structured interviews. A non-probability purposive sampling was adopted, drawing a sample of 20 participants for surveys representing 20 NGOs and 15 participants for face-to-face structured interviews representing 10 NGOs. The survey responses were analysed using spreadsheet (excel) while face to face interviews were analysed using NVivo Software, following Tech's (1990) process for data analysis. The study sought to answer questions centred around financial management, financial sustainability, sound financial management practices, sources of income and alternative funding for NGOs in Botswana. The main findings demonstrate a great understanding of financial management and financial sustainability. They also showed a strong practice of financial planning enhanced by strategic planning and budgeting. A strong financial recording process which includes the use of accounting process, systems, and tools. On the other hand, somewhat a weak financial monitoring process, with good use of audits but reluctancy in reviewing financial statements. Moreover, the results illustrate diverse but weak income sources, shown by a decline in local and international funding. Lastly the study shows the presence of an alternative funding approach which has ensured some income generation. On the same note NGOs have low financial reserves and survival ratios. The study recommends the strengthening of NGOs financial capacity, by NGOs, the private sector, and the government. NGOs should prioritise sound financial management and improve their financial capacity. The private sector and other stakeholders should promote sustainable financial support and partnerships with NGOs. The government should view NGOs as key partners and actively support their mandate. NGOs should prioritise financial management, train and enhance capacity of their members to ensure financial prudence.